Transforming violent conflict radical disagreement, dialogue and survival - Ramsbotham, Oliver (Routledge, 2010)
This title explores methods of managing radical disagreement and creating dialogues in violent and intractable conflicts, using the Israeli-Palestinian conflict as context.
Keywords: Sociolinguistics; Social conflict; Violence; Discourse analysis; Conflict (Psychology); Human behavior; Diskursanalyse; Konfliktlösung; Soziolinguistik; Politischer Konflikt